PURIFICATION OF BIODIESEL USING RICE STRAW AND DIOSCOREA ALATA STARCH AS NATURAL ADSORBENTS - Yulidar Yulidar; Saiful Saiful; Ilham Maulana (Jurnal Natural, 2019)
Janeng starch (Dioscorea Alata) and rice straws are developed to be used as adsorbents in dry washing method to purify crude biodiesel. In this study, we evaluate the potential of rice straw and janeng starch as natural adsorbents in the purification of biodiesel that replace the role of water in absorbing contaminants from biodiesel. The SEM characterization results show that the starch adsorbent and rice straw has an open and porous surface and is evenly distributed for janeng starch. Both adsorbents, either the janeng starch or rice straw, can be applied for the purification of biodiesel. The quality of biodiesel is influenced by the amount of adsorbents used in biodiesel purification. The effectiveness of the adsorbent is shown by the decrease in free fatty acids, alkali numbers, soap numbers and turbidity levels in biodiesel. The concentration of free fatty acid oil in crude biodiesel before the purification step was 0.769 mg-KOH/g, then decreased to 0.128 mg-KOH/g after the adsorption. This acid value had been very low and met the Indonesian quality national standard for biodiesel spesically 0.50 mg-KOH/g. Either janeng starch or rice straw adsorbent was able to reduce the soap content of potassium oleate to level 53.33 ppm from the initial content of 106.67 ppm. These two natural adsorbents can be the alternative adsorbents in the purification of biodiesel that employs dry washing method.